Wear-resistant photo-thermal super-hydrophobic coating and preparation method thereof

By mixing SiO2 nanoparticles and candle soot to form a super-hydrophobic coating, and spraying it on the substrate, it solves the problems of complex preparation and easy wear of the existing candle soot coating, and realizes the preparation of wear-resistant photothermal super-hydrophobic coating, which has Excellent photothermal anti-icing performance and long-term wear resistance.

CN119307126APending Publication Date: 2025-01-14CHANGZHOU UNIV

Patent Information

Application Number
CN202411691209.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing candle ash coating preparation methods are complex, easy to wear, low hydrophobicity and mechanical strength, making it difficult to maintain long-term wear-resistant photothermal superhydrophobic properties in harsh environments.

Method used

SiO2 nanoparticles and dispersant are dispersed in deionized water, and a fluorine-containing silane coupling agent is added to form a fluorine-modified SiO2 dispersion. Candle soot is deposited and dispersed ultrasonically to form a super hydrophobic coating, which is sprayed on the pretreated base. On the material, after drying, a wear-resistant light-heat super-hydrophobic coating is obtained.

Benefits of technology

The process is simple and the coating has good photothermal properties, super hydrophobic properties and abrasion resistance, which significantly improves the adhesion and durability of candle soot and solves the problems of traditional coatings being easy to wipe and not wear-resistant. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307126A_ABST
    Figure CN119307126A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a wear-resistant photo-thermal super-hydrophobic coating, and the preparation method comprises the following steps: (1) adding SiO2 nanoparticles and a dispersant into deionized water for dispersion, then adding a fluorine-containing silane coupling agent, and fully stirring to obtain a fluorine-modified SiO2 dispersion liquid; (2) depositing candle ash, adding the obtained candle ash into the fluorine-modified SiO2 dispersion liquid, performing ultrasonic dispersion, and performing stirring reaction to obtain a super-hydrophobic coating; and (3) spraying the obtained super-hydrophobic coating on a pretreated base material, and drying to obtain the wear-resistant photo-thermal super-hydrophobic coating. The process method is simple, and the obtained coating has good photo-thermal performance, super-strong hydrophobic performance and abrasion resistance and excellent photo-thermal anti-icing performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of super-hydrophobic materials, and in particular to a wear-resistant photothermal super-hydrophobic coating and a preparation method thereof. Background Art

[0002] Ice on wind turbines increases the weight of blades and affects power generation efficiency, which leads to a decrease in aerodynamic performance, reduces the efficiency of wind power generation, increases mechanical burden, and causes noise. Anti-icing coating is an ideal anti-icing method with low energy consumption and no pollution.

[0003] The surface of superhydrophobic materials is mainly composed of micron / nano structures and low surface energy, which can effectively prevent ice nucleation, delay ice accumulation and reduce ice adhesion after freezing. CN201510661330.X discloses a method for preparing superhydrophobic silica particles and superhydrophobic coatings. G. Josh et al. disclose a coating composition with superhydrophobic and oleophobic surfaces prepared by fluoropolymers (G. Josh, et al. Superhydrophobic and oleophobic coatings with low VOC binder systems. AU2012220798A[A]. 2013-10-10), combining silica and fluoropolymers to form a superhydrophobic surface, which can effectively inhibit the adhesion of water and ice.

[0004] However, under sub-zero conditions, ice can simply form on superhydrophobic surfaces. Once ice interlocks with the micro / nanostructures, the superhydrophobic surface loses its hydrophobicity, resulting in increased ice adhesion. Studies have shown that combining superhydrophobicity with photothermal treatment can effectively prevent ice nucleation, delay ice accumulation, and even melt accumulated ice.

[0005] Candle ash has excellent photothermal properties and is environmentally friendly and cheap. For example, Chinese patent CN202210052383.1 discloses a superhydrophobic photothermal coating, its preparation method and application. However, the candle ash coating formed by the patent has weak adhesion and poor durability. HK Do et al. proposed a method for preparing a candle ash coating, which uses a cooling liquid to coat the back of a substrate and intermittently cools the candle during carbonization (HK Do, et al. Fabrication method of a stable superhydrophobic surface through the fixation of nanoparticle by using a paraffin wax. KR20130124203[B]. 2014-10-08). The process of this method is complicated, and the obtained candle ash particles have weak adhesion and are easy to wear. TF Qahtan et al. disclosed a method for preparing a photothermal superhydrophobic coating, in which the collected candle soot was made into a solution, and the solution was directly sprayed on a substrate to prepare a photothermal superhydrophobic coating (TF Qahtan, et al. Fabrication of Water Jet Resistant and Thermally Stable Superhydrophobic Surfaces by Spray Coating of Candle Soot Dispersion[J], Sci Rep 7 (2017) 7531). However, the coating prepared by this method has poor hydrophobicity and low mechanical strength. Under long-term use or harsh environment (such as acid rain corrosion, mechanical wear), the coating structure is very easy to be damaged, and the hydrophobicity and anti-icing performance are significantly reduced. Therefore, the development of a photothermal superhydrophobic candle ash coating with long-term wear resistance is a technical problem in this field. Summary of the invention

[0006] In order to solve the technical problems of the existing candle ash coating, such as complex preparation method, easy wear, low hydrophobicity and mechanical strength, the present invention provides a wear-resistant photothermal super hydrophobic coating and a preparation method thereof.

[0007] The technical solution adopted by the present invention is: A method for preparing a wear-resistant photothermal super-hydrophobic coating comprises the following steps: (1) adding SiO2 nanoparticles and a dispersant into deionized water for dispersion, then adding a fluorine-containing silane coupling agent and stirring thoroughly to obtain a fluorine-modified SiO2 dispersion; (2) depositing candle ash, adding the obtained candle ash into a fluorine-modified SiO2 dispersion, and obtaining a super-hydrophobic coating after ultrasonic dispersion and stirring reaction; (3) The obtained super hydrophobic coating is sprayed on the pretreated substrate, and after drying, a wear-resistant photothermal super hydrophobic coating is obtained.

[0008] Furthermore, the dispersant is polyethylene glycol.

[0009] Furthermore, the fluorine-containing silane coupling agent is heptadecafluorodecyltrimethoxysilane.

[0010] Furthermore, the mass fraction of the SiO2 nanoparticles in the fluorine-modified SiO2 dispersion is 2-4wt%, the mass fraction of the dispersant in the fluorine-modified SiO2 dispersion is 2-3wt%, the mass fraction of the candle ash in the fluorine-modified SiO2 dispersion is 0.1-0.4wt%, and the mass fraction of the fluorine-containing silane coupling agent in the fluorine-modified SiO2 dispersion is 2-4wt%.

[0011] Furthermore, the method for depositing candle ash is: placing a high temperature resistant container upside down directly above the candle flame, with the bottom of the high temperature resistant container being 5 to 10 cm away from the center of the candle flame.

[0012] Furthermore, the substrate is a glass fiber board, and the pretreatment method is to use solvent washing to remove impurities and oil stains, sandblasting after washing, and then ultrasonic cleaning, and then placing it in a drying oven to dry.

[0013] Furthermore, in step (1), the dispersion time is 40 to 60 minutes; the stirring speed is 1000 to 1200 rpm, and the stirring time is 24 to 36 hours.

[0014] Furthermore, in step (2), the ultrasonic time is 20-30 min, the stirring speed is 500-600 rpm, and the stirring time is 10-15 min.

[0015] Furthermore, in step (3), the spray gun pressure is 0.5-0.7 MPa, the spray gun is 10-15 cm away from the substrate; the drying temperature is 60-80° C., and the drying time is 9-12 h.

[0016] A wear-resistant photothermal super-hydrophobic coating prepared by any of the above preparation methods.

[0017] Beneficial effects of the present invention: (1) The present invention forms a super-hydrophobic coating by mixing candle soot produced by incomplete combustion and fluorinated SiO2 nanoparticles, and prepares the super-hydrophobic coating by spraying. The process is simple, and the obtained coating has good photothermal properties, super strong hydrophobic properties and abrasion resistance, and excellent photothermal anti-icing properties.

[0018] (2) The present invention uses glass fiber board as the substrate to prepare the coating. The silane group (-Si(OEt)3) in the fluorinated silica particles reacts with the hydroxyl group (-OH) on the surface of the glass fiber board to form a silicon-oxygen bond (Si-O-Si), thereby achieving strong adhesion between the coating and the substrate. At the same time, the silane group forms a chemical bond with the carbon atoms in the candle ash, thereby enhancing the adhesion and durability of the candle ash, thereby solving the technical problem of the traditional method that the candle ash is easy to wipe and not wear-resistant.

[0019] (3) The candle ash in the coating can provide a porous roughness skeleton, and the fluorinated SiO2 nanoparticles are evenly dispersed and filled in the tiny pores to form a micro / nano multi-level nested structure, achieving the enhanced effect of component and structure coupling, significantly reducing the surface energy, enhancing the surface anti-wetting ability, and solving the bottleneck problem of poor hydrophobicity of existing candle ash coatings. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a scanning electron microscope image of the microscopic morphology of the coating surface prepared in Example 1.

[0021] Figure 2 The water contact angle diagrams of the super-hydrophobic coatings prepared in Examples 1-5 and Comparative Examples 1-2 of the present invention.

[0022] Figure 3 The temperature rise curves of the super-hydrophobic coatings prepared in Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention are shown.

[0023] Figure 4 The temperature rise curve of Example 1 of the present invention under 0.5, 1, and 1.5 sun illumination intensities is shown.

[0024] Figure 5 This is a temperature rise / fall curve diagram of Example 1 under 1 sun illumination intensity for 10 cycles. DETAILED DESCRIPTION

[0025] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0026] The methods used in the present invention are conventional methods unless otherwise specified, and the reagents used in the present invention are commercially available products unless otherwise specified. Example 1

[0027] (1) A 1 cm × 1 cm × 0.2 cm glass fiber board was immersed in an ethanol solution and subjected to ultrasonic treatment to remove impurities and oil stains on the surface of the substrate. The treated glass fiber board was sandblasted, and then cleaned with an ultrasonic cleaner for 10 minutes, and then dried in a drying oven at 60°C for 3 hours.

[0028] (2) 1 g of SiO2 nanoparticles and 1 g of polyethylene glycol were added to 45.9 g of deionized water, and the SiO2 suspension was dispersed by an ultrasonic oscillator for 60 min. Finally, 2 g of heptadecafluorodecyltrimethoxysilane was added to the ultrasonically treated SiO2 suspension, and then the suspension was vigorously stirred at 1000 rpm for 24 h using a magnetic stirrer to obtain a fluorinated SiO2 dispersion.

[0029] (3) Light a commercially available candle, wait for the flame to stabilize, and then place a heat-resistant container upside down directly above the candle flame, with the bottom of the heat-resistant container 8 cm away from the center of the candle flame. Because of the obstruction of the bottom of the cup, the candle burns incompletely, producing a large amount of hydrophobic carbon soot particles that accumulate at the bottom of the cup. Then, take out 0.1 g of candle ash from the heat-resistant container and add it to the fluorinated SiO2 suspension, then disperse it with an ultrasonic oscillator for 20 minutes, and then stir it with a magnetic stirrer at 500 rpm for 10 minutes to obtain the desired candle ash and SiO2 mixed suspension.

[0030] (4) Lay the pretreated fiberglass substrate flat, and use a spray gun to spray the candle ash and SiO2 mixed suspension on the substrate surface. The spray gun pressure is 0.6MPa, and the spray gun is 15cm away from the substrate. Then place the fiberglass substrate sprayed with the suspension in a drying oven at a temperature of 60℃, pre-cure for 1h, then set the drying oven temperature to 80℃, and cure for 8h to obtain the wear-resistant photothermal super hydrophobic coating A. Its electron microscope image is shown in Figure 1 .

[0031] from Figure 1 It can be seen that the SiO2 particles and candle ash particles are well combined together, and the overall structure shows a high surface roughness, which plays an important role in superhydrophobicity. The rough surface can capture air, form a stable hydrophobic layer, and enhance the hydrophobic effect. Example 2

[0032] (1) A 1 cm × 1 cm × 0.2 cm glass fiber board was immersed in an ethanol solution and subjected to ultrasonic treatment to remove impurities and oil stains on the surface of the substrate. The treated glass fiber board was sandblasted, and then the glass fiber board was cleaned with an ultrasonic cleaner for 10 minutes, and then dried in a drying oven at 60°C for 3 hours.

[0033] (2) 1 g of SiO2 nanoparticles and 1 g of polyethylene glycol were added to 46.8 g of deionized water, and the SiO2 suspension was dispersed by an ultrasonic oscillator for 60 min. Finally, 1 g of heptadecafluorodecyltrimethoxysilane was added to the ultrasonically treated SiO2 suspension, and then vigorously stirred at 1000 rpm for 24 h using a magnetic stirrer to obtain a fluorinated SiO2 dispersion.

[0034] (3) Light a commercially available candle, wait for the flame to stabilize, and then place a heat-resistant container upside down directly above the candle flame, with the bottom of the heat-resistant container 8 cm away from the center of the candle flame. Because of the obstruction of the bottom of the cup, the candle burns incompletely, producing a large amount of hydrophobic carbon soot particles that accumulate at the bottom of the cup. Then, take out 0.2 g of candle ash from the heat-resistant container and add it to the fluorinated SiO2 suspension. Use an ultrasonic oscillator to disperse it for 30 minutes, and then use a magnetic stirrer to stir at 600 rpm for 15 minutes to obtain the desired candle ash and SiO2 mixed suspension.

[0035] (4) Lay the pretreated fiberglass substrate flat, and use a spray gun to spray the candle ash and SiO2 mixed suspension on the substrate surface. The spray gun pressure is 0.5MPa, and the spray gun is 15cm away from the substrate. Then place the fiberglass substrate sprayed with the suspension in a drying oven at a temperature of 60℃, pre-cure for 1h, then set the drying oven temperature to 80℃, and cure for 8h to obtain the wear-resistant photothermal super hydrophobic coating B. Example 3

[0036] (1) A 1 cm × 1 cm × 0.2 cm glass fiber board was immersed in an ethanol solution and subjected to ultrasonic treatment to remove impurities and oil stains on the surface of the substrate. The treated glass fiber board was sandblasted, and then cleaned with an ultrasonic cleaner for 10 minutes, and then dried in a drying oven at 60°C for 3 hours.

[0037] (2) 1 g of SiO2 nanoparticles and 1 g of polyethylene glycol were added to 46.95 g of deionized water, and the SiO2 suspension was dispersed by an ultrasonic oscillator for 60 min. Finally, 1 g of heptadecafluorodecyltrimethoxysilane was added to the ultrasonically treated SiO2 suspension, and then the suspension was vigorously stirred at 1000 rpm for 24 h using a magnetic stirrer to obtain a fluorinated SiO2 dispersion.

[0038] (3) Light a commercially available candle, wait for the flame to stabilize, and then place a heat-resistant container upside down directly above the candle flame, with the bottom of the heat-resistant container 8 cm away from the center of the candle flame. Because of the obstruction of the bottom of the cup, the candle burns incompletely, producing a large amount of hydrophobic carbon soot particles that accumulate at the bottom of the cup. Then, take out 0.05 g of candle ash from the heat-resistant container and add it to the fluorinated SiO2 suspension. Use an ultrasonic oscillator to disperse it for 30 minutes, and then use a magnetic stirrer to stir at 500 rpm for 10 minutes to obtain the desired candle ash and SiO2 mixed suspension.

[0039] (4) Lay the pretreated fiberglass substrate flat, and use a spray gun to spray the candle ash and SiO2 mixed suspension on the substrate surface. The spray gun pressure is 0.6MPa, and the spray gun is 15cm away from the substrate. Then place the fiberglass substrate sprayed with the suspension in a drying oven at a temperature of 60℃, pre-cure for 1h, then set the drying oven temperature to 80℃, and cure for 8h to obtain the wear-resistant photothermal super hydrophobic coating C. Example 4

[0040] (1) A 1 cm × 1 cm × 0.2 cm glass fiber board was immersed in an ethanol solution and subjected to ultrasonic treatment to remove impurities and oil stains on the surface of the substrate. The treated glass fiber board was sandblasted, and then cleaned with an ultrasonic cleaner for 10 minutes, and then dried in a drying oven at 60°C for 3 hours.

[0041] (2) 2 g of SiO2 nanoparticles and 1.5 g of polyethylene glycol were added to 45.4 g of deionized water, and the SiO2 suspension was dispersed by ultrasonic oscillator for 60 min. Finally, 1 g of heptadecafluorodecyltrimethoxysilane was added to the ultrasonically treated SiO2 suspension, and then vigorously stirred at 1200 rpm for 24 h using a magnetic stirrer to obtain a fluorinated SiO2 dispersion.

[0042] (3) Light a commercially available candle, wait for the flame to stabilize, and then place a heat-resistant container upside down directly above the candle flame, with the bottom of the heat-resistant container 10 cm away from the center of the candle flame. Because of the obstruction of the bottom of the cup, the candle burns incompletely, producing a large amount of hydrophobic carbon soot particles that accumulate at the bottom of the cup. Then, take out 0.1 g of candle ash from the heat-resistant container and add it to the fluorinated SiO2 suspension. Then, use an ultrasonic oscillator to disperse the candle ash for 20 minutes, and then use a magnetic stirrer to stir at 500 rpm for 10 minutes to obtain the desired candle ash and SiO2 mixed suspension.

[0043] (4) Lay the pretreated fiberglass substrate flat, and use a spray gun to spray the candle ash and SiO2 mixed suspension on the substrate surface. The spray gun pressure is 0.7MPa, and the spray gun is 15cm away from the substrate. Then place the fiberglass substrate sprayed with the suspension in a drying oven at a temperature of 60℃, pre-cured for 1h, and then set the drying oven temperature to 80℃ and cured for 11h to obtain the wear-resistant photothermal super hydrophobic coating D. Example 5

[0044] (1) A 1 cm × 1 cm × 0.2 cm glass fiber board was immersed in an ethanol solution and subjected to ultrasonic treatment to remove impurities and oil stains on the surface of the substrate. The treated glass fiber board was sandblasted, and then cleaned with an ultrasonic cleaner for 10 minutes, and then dried in a drying oven at 60°C for 3 hours.

[0045] (2) 1 g of SiO2 nanoparticles and 1 g of polyethylene glycol were added to 45.9 g of deionized water, and the SiO2 suspension was dispersed by an ultrasonic oscillator for 60 min. Finally, 2 g of heptadecafluorodecyltrimethoxysilane was added to the ultrasonically treated SiO2 suspension, and then vigorously stirred at 1000 rpm for 36 h using a magnetic stirrer to obtain a fluorinated SiO2 dispersion.

[0046] (3) Light a commercially available candle, wait for the flame to stabilize, and then place a heat-resistant container upside down directly above the candle flame, with the bottom of the heat-resistant container 5 cm away from the center of the candle flame. Because of the obstruction of the bottom of the cup, the candle burns incompletely, producing a large amount of hydrophobic carbon soot particles that accumulate at the bottom of the cup. Then, take out 0.1 g of candle ash from the heat-resistant container and add it to the fluorinated SiO2 suspension. Then, use an ultrasonic oscillator to disperse the candle ash for 20 minutes, and then use a magnetic stirrer to stir at 500 rpm for 10 minutes to obtain the desired candle ash and SiO2 mixed suspension.

[0047] (4) Lay the pretreated fiberglass substrate flat, and use a spray gun to spray the candle ash and SiO2 mixed suspension on the substrate surface. The spray gun pressure is 0.6MPa, and the spray gun is 15cm away from the substrate. Then place the fiberglass substrate sprayed with the suspension in a drying oven at a temperature of 60℃, pre-cure for 1h, then set the drying oven temperature to 80℃, and cure for 8h to obtain the wear-resistant photothermal super hydrophobic coating E.

[0048] Comparative Example 1 (1) A 1 cm × 1 cm × 0.2 cm glass fiber board was immersed in an ethanol solution and subjected to ultrasonic treatment to remove impurities and oil stains on the surface of the substrate. The treated glass fiber board was sandblasted, and then cleaned with an ultrasonic cleaner for 10 minutes, and then dried in a drying oven at 60°C for 3 hours.

[0049] (2) 1 g of SiO2 nanoparticles and 1 g of polyethylene glycol were added to 47 g of deionized water, and the SiO2 suspension was dispersed by ultrasonic oscillator for 60 min. Finally, 1 g of heptadecafluorodecyltrimethoxysilane was added to the ultrasonically treated SiO2 suspension, and then vigorously stirred at 1000 rpm for 24 h using a magnetic stirrer to obtain a fluorinated SiO2 dispersion.

[0050] (3) Lay the pretreated fiberglass substrate flat, and spray the SiO2 suspension on the substrate surface with a spray gun. The spray gun pressure is 0.6MPa, and the spray gun is 15cm away from the substrate. Then place the fiberglass substrate sprayed with the suspension in a drying oven at a temperature of 60°C, pre-cure for 1h, then set the drying oven temperature to 80°C, and cure for 8h to obtain a silica hydrophobic coating.

[0051] Comparative Example 2 (1) A 1 cm × 1 cm × 0.2 cm glass fiber board was immersed in an ethanol solution and subjected to ultrasonic treatment to remove impurities and oil stains on the surface of the substrate. The treated glass fiber board was sandblasted, and then cleaned with an ultrasonic cleaner for 10 minutes, and then dried in a drying oven at 60°C for 3 hours.

[0052] (2) Light a commercially available candle and wait for the flame to stabilize. Place the pretreated fiberglass board flat at a distance of 8 cm from the center of the candle flame, with the pretreated surface facing the candle. Deposit a candle ash super-hydrophobic coating on the treated surface of the fiberglass board. Brush the untreated surface of the fiberglass board with water to prevent thermal deformation of the substrate. During the deposition process, drip water onto the untreated surface to cool it down, thus obtaining a candle ash coating.

[0053] The samples prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were tested for hydrophobicity, photothermal performance, and wear resistance. The results are shown in Tables 1 and Figure 1-Figure 5 shown.

[0054] The wear resistance test is to place the test sample flat on sandpaper, apply a 50g weight to the sample and slide it for 100cm. The water contact angle results of the sample surface after testing are shown in Table 1.

[0055] .

[0056] As can be seen from Table 1: the hydrophobic angle of the wear-resistant photothermal super-hydrophobic coating prepared by the present invention is above 155°, and the hydrophobic angle after wear is above 141°. The hydrophobic angle of the pure SiO2 coating prepared in Comparative Example 1 is 155.5°, and the water contact angle after wear is 132°. The hydrophobic angle of the candle soot coating prepared in Comparative Example 2 is 149.1°, and the water contact angle after wear is 91°. The wear resistance of the pure candle soot coating is extremely poor. The reason for this is that the pressure causes a sharp destruction of the anti-wetting property of the coating surface, resulting in almost no candle soot on the substrate surface, resulting in a significant decrease in the hydrophobic angle. The wear resistance of the pure silica coating is also poor, and the hydrophobic angle is significantly reduced. The hydrophobic angle after wear is only 132°. Compared with Comparative Examples 1-2, the SiO2 / CS coating of the present invention still has a minimum water contact angle of 146° after sliding 100cm, and can still maintain its super-hydrophobicity, indicating that the wear resistance and hydrophobicity of the coating prepared by mixing candle soot and silica are greatly improved.

[0057] Figure 3 The temperature rise curves of the super hydrophobic coatings prepared in Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention are shown in FIG. Figure 3 It can be seen that with the extension of illumination time, the surface temperature rises sharply. And the higher the mass fraction of candle ash in the coating, the faster the surface heating rate under sunlight, and the faster the surface ice can be removed. Within 10 minutes of sunlight exposure, the surface temperature of Comparative Example 1 only rose from 27.0°C to 40.9°C, while the surface temperature of Example 3 of the present invention increased from 27°C to 55°C, which was 1.2°C higher than Comparative Example 1. The surface temperature of Examples 1 and 2 rose from 27°C to 66.4°C, and the maximum heating rate could reach 30°C / min. The present invention exhibits excellent photothermal performance.

[0058] Figure 4 The temperature rise curves of Example 1 under 0.5, 1, and 1.5 solar illumination intensities are shown in FIG. Figure 4 It can be seen that SiO2 / CS2 can still reach 45.3℃ even at an intensity of only 0.5 suns, and can maintain a certain temperature even in a low temperature environment, and can reach a high temperature of 78℃ at an intensity of 1.5 suns.

[0059] Figure 5 The temperature rise / fall curve of Example 1 in 10 cycles under 1 sun illumination intensity. Figure 5 It can be seen that after 10 consecutive high and low temperature changes, SiO2 / CS2 can still reach a maximum temperature of 60°C, reflecting the excellent durability and reliability of the coating of the present invention in repeated temperature changes.

[0060] The above-described embodiment is only a preferred solution of the present invention, but it is not intended to limit the present invention. A person skilled in the relevant technical field may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, any technical solution obtained by equivalent replacement or equivalent transformation falls within the protection scope of the present invention.

Claims

1. A method for preparing a wear-resistant photothermal super-hydrophobic coating, characterized in that: The steps include: (1) adding SiO2 nanoparticles and a dispersant into deionized water for dispersion, then adding a fluorine-containing silane coupling agent and stirring thoroughly to obtain a fluorine-modified SiO2 dispersion; (2) depositing candle ash, adding the obtained candle ash into a fluorine-modified SiO2 dispersion, and obtaining a super-hydrophobic coating after ultrasonic dispersion and stirring reaction; (3) The obtained super hydrophobic coating is sprayed on the pretreated substrate, and after drying, a wear-resistant photothermal super hydrophobic coating is obtained.

2. A method for preparing a wear-resistant photothermal super-hydrophobic coating according to claim 1, characterized in that, The dispersant is polyethylene glycol.

3. A method for preparing a wear-resistant photothermal super-hydrophobic coating according to claim 1, characterized in that, The fluorine-containing silane coupling agent is heptadecafluorodecyltrimethoxysilane.

4. A method for preparing a wear-resistant photothermal super-hydrophobic coating according to claim 1, characterized in that, The mass fraction of the SiO2 nanoparticles in the fluorine-modified SiO2 dispersion is 2-4wt%, the mass fraction of the candle ash in the fluorine-modified SiO2 dispersion is 0.1-0.4wt%, the mass fraction of the dispersant in the fluorine-modified SiO2 dispersion is 2-3wt%, and the mass fraction of the fluorine-containing silane coupling agent in the fluorine-modified SiO2 dispersion is 2-4wt%.

5. A method for preparing a wear-resistant photothermal super-hydrophobic coating according to claim 1, characterized in that, The method for depositing candle ash is: turn the high temperature resistant container upside down just above the candle flame, with the bottom of the high temperature resistant container 5 to 10 mm away from the center of the candle flame.

6. A method for preparing a wear-resistant photothermal super-hydrophobic coating according to claim 1, characterized in that, The substrate is a glass fiber board, and the pretreatment method is to use solvent washing to remove impurities and oil stains, sandblasting after washing, and then ultrasonic cleaning, and then placing in a drying oven to dry.

7. A method for preparing a wear-resistant photothermal super-hydrophobic coating according to claim 1, characterized in that, In step (1), the dispersion time is 40 to 60 minutes; the stirring speed is 1000 to 1200 rpm, and the stirring time is 24 to 36 hours.

8. A method for preparing a wear-resistant photothermal super-hydrophobic coating according to claim 1, characterized in that, In step (2), the ultrasonic time is 20-30 min, the stirring speed is 500-600 rpm, and the stirring time is 10-15 min.

9. A method for preparing a wear-resistant photothermal super-hydrophobic coating according to claim 1, characterized in that, In step (3), the spray gun pressure is 0.5-0.7 MPa, and the spray gun is 10-15 cm away from the substrate; the drying temperature is 60-80°C, and the drying time is 9-12 h.

10. A wear-resistant photothermal super-hydrophobic coating prepared according to the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Large-scale preparation method of transparent super-hydrophobic / super-amphiphobic coating

    CN106800885A

  • Durable super-hydrophobic candle ash coating and preparation method thereof

    CN114082624A

  • Cage silsesquioxane spherical nanoparticles with controllable surface wettability as well as preparation method and application of cage silsesquioxane spherical nanoparticles

    CN117126402A

  • Flexible super-hydrophobic film with photothermal effect and electrothermal effect as well as preparation method and application of flexible super-hydrophobic film

    CN117924780A

  • Super-hydrophobic coating agent and manufacturing method thereof

    KR1020160099952A

Cited By

  • Potassium-tungsten bronze-based photo-thermal super-hydrophobic coating as well as preparation method and application thereof

    CN122381623A